A rare case of Bordetella avium pneumonia complicated by Raoultella planticola - Anna Lavrenko (Clinical Case Reports, 2020)
Abstract Bordetella avium pneumonia immunocompromised the patient with subsequent complication by a rare opportunistic Raoultella planticola infection, which became a nosocomial pathogen in the healthcare setting.